Emprego de matriz óssea orgânica bovina e hidroxiapatita no reparo de defeito induzido em crânio de ratos - Braz, Fabiano [UNESP] (2003)
PURPOSE: The aim of this study was to evaluate the biological response and inductor effect of the hydroxyapatite combined with bovine organic bone matrix. METHODS: Skull defects were induced on 20 male albino rats, with initial body weight between 300 and 350 grams. The animals were divided into two groups. In group I the defect was filled with hydroxyapatite combined with bovine organic bone matrix, and in group II no product was used. Five animals of each group were euthanised 30 and 60 days after the surgery for histopathological evaluation. RESULTS: Bone reabsorption was more evident in the group II at 30 days post surgery. There was no difference on presence of cartilage between moments in the same group. Statistical difference was observed between group I and II at 30 days after the surgery. At day 60 post surgery, animals from group I showed a higher quantity of osteoblasts and cartilage compare to group II. CONCLUSION: It was possible to conclude that hydroxyapatite combined with bovine organic bone matrix does not produce adverse reaction and induce bone repair.